2018
DOI: 10.1080/14616734.2018.1433696
|View full text |Cite
|
Sign up to set email alerts
|

Middle Childhood Attachment Strategies: validation of an observational measure

Abstract: The purpose of this study was to assess behavioral manifestations of attachment in middle childhood, and to evaluate their relations with key theoretical correlates. The sample consisted of 87 children (aged 10-12 years) and their mothers. Dyads participated in an 8-min videotaped discussion of a conflict in their relationships, later scored with the Middle Childhood Attachment Strategies Coding System (MCAS) for key features of all child attachment patterns described in previous literature (secure, ambivalent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 58 publications
1
23
0
2
Order By: Relevance
“…During middle childhood, ABC has been shown to positively affect physiological regulation (Tabachnick et al, ) and brain development (Bick et al, ). Given that several studies demonstrate that children with secure perceptions of their parents show more competent adaptation in school contexts (Brumariu, Giuseppone et al, ; Brumariu, Madigan et al, ), exhibit more emotional and peer social competence (Brumariu, Giuseppone et al, ; Brumariu & Kerns, ; Brumariu & Kerns, ; Brumariu, Kerns, & Seibert, ; Brumariu, Madigan et al, ; Kerns et al, ; Madigan et al, ), have higher self‐esteem (Brumariu, Giuseppone et al, ; Brumariu, Madigan et al, ), and exhibit fewer behavioral problems than children with insecure perceptions (Brumariu, Giuseppone et al, ; Brumariu, Madigan et al, ; Madigan et al, ), it is encouraging that ABC's effects on attachment are sustained in middle childhood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During middle childhood, ABC has been shown to positively affect physiological regulation (Tabachnick et al, ) and brain development (Bick et al, ). Given that several studies demonstrate that children with secure perceptions of their parents show more competent adaptation in school contexts (Brumariu, Giuseppone et al, ; Brumariu, Madigan et al, ), exhibit more emotional and peer social competence (Brumariu, Giuseppone et al, ; Brumariu & Kerns, ; Brumariu & Kerns, ; Brumariu, Kerns, & Seibert, ; Brumariu, Madigan et al, ; Kerns et al, ; Madigan et al, ), have higher self‐esteem (Brumariu, Giuseppone et al, ; Brumariu, Madigan et al, ), and exhibit fewer behavioral problems than children with insecure perceptions (Brumariu, Giuseppone et al, ; Brumariu, Madigan et al, ; Madigan et al, ), it is encouraging that ABC's effects on attachment are sustained in middle childhood.…”
Section: Discussionmentioning
confidence: 99%
“…The Security Scale is a self‐report questionnaire that assesses children's perceived attachment security to a particular parent. It is a moderately stable and robust measure of attachment in middle childhood and early adolescence and has been shown to be significantly associated with other measures of attachment (e.g., Strange Situation) and parental sensitivity (see Brumariu, Giuseppone et al, ; Brumariu, Madigan et al, for a review). Additionally, scores on the Security Scale are positively associated with school adaptation, emotional competence, and peer competence, and negatively associated with internalizing and externalizing symptoms (Brumariu, Giuseppone et al, ; Brumariu, Madigan et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Because of this development, it has been suggested that the evaluation of the attachment system in middle childhood ought to also include other important individuals besides the parents, for instance best friends (e.g., Psouni & Apetroaia, ; Verschueren & Koomen, ). At the same time, even though the independence and social world of children in middle childhood grow, parents are most often still the primary attachment figures (Brumariu, Giuseppone, Kerns et al ., ; Kerns & Brumariu, ; Kerns, Tomich & Kim, ; Seibert & Kerns, ). Crucially, with the acquisition of language, which is well‐established by the early school years, and the development of metacognitive skills in middle childhood, children can also begin to think and reflect about their experiences in attachment and other close relationships, making possible a remodeling of their early mental representations of attachment (Kriss, Steele & Steele, ).…”
Section: Introductionmentioning
confidence: 99%
“…The issue of measurement of attachment in middle childhood remains more unsettled, as the upsurge of attention towards attachment in middle childhood from researchers and clinicians during the last decade has led to the development of several different measures, with varying focus and underlying assumptions, and few studies have scrutinized whether and how these different measures converge (e.g., Di Folco, Messina, Zavattini & Psouni, ; Psouni & Apetroaia, ). While attachment questionnaires elicit descriptions of behaviors with parents (e.g., the Security Scale: Kerns, Aspelmeier, Gentzler & Grabill, ), behavioral measures follow the paradigm used for attachment assessment in infancy and early childhood and observe the child’s behavior towards a specific caregiver, in situations likely to activate the attachment system (see Boldt, Kochanska, Grekin & Brock, ; Brumariu et al ., ; Bureau, Easterbrooks & Lyons‐Ruth, ). Adopting a representational focus, narrative‐based measures use carefully selected word‐probes and attachment‐related story themes to access children’s (implicit) attachment scripts as components of their attachment representations (e.g., the Secure Base Script Test: Psouni & Apetroaia, ).…”
Section: Introductionmentioning
confidence: 99%
“…Weiser suggested that an excellent strategy to collect data in Ubicomp systems is to follow work from psychology and anthropology (Weiser, 1993). Systematic observation and coding of behaviours is a well‐known technique borrowed from psychology research (Borges, Falcón, & Díaz, 2016; Maclin & Maclin, 2005; Pesch & Lumeng, 2017) and widely used by some researchers to evaluate systems' impact of use (Brumariu et al, 2018; Caro, 2014; Consolvo, Arnstein, & Franza, 2002; Escobedo et al, 2012; Escobedo, Tentori, Quintana, Favela, & Garcia‐Rosas, 2014; Radu, Guzdial, & Avram, 2017). The technique provides a unique glance into user behaviours that can yield rich quantitative and qualitative data.…”
Section: Introductionmentioning
confidence: 99%